Making National News A History of Canadian Press - Allen, Gene (University of Toronto Press, 2017)
For almost a century, Canadian newspapers, radio and television stations, and now internet news sites have depended on the Canadian Press news agency for most of their Canadian (and, through its international alliances) foreign news. This book provides the first-ever scholarly history of CP, as well as the most wide-ranging historical treatment of twentieth-century Canadian journalism published to date.Using extensive archival research, including complete and unfettered access to CP’s archives, Gene Allen traces how CP was established and evolved in the face of frequent conflicts among the powerful newspaper publishers – John Ross Robertson, Joseph Atkinson, and Roy Thomson, among others – who collectively owned it, and how the journalists who ran it understood and carried out their work. Other major themes include CP’s shifting relationships with the Associated Press and Reuters; its responses to new media; its aggressive shaping of its own national role during the Second World War; and its efforts to meet the demands of French-language publishers.Making National News makes a substantial and original contribution to our understanding of journalism as a phenomenon that shaped Canada both culturally and politically in the twentieth century
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: Geschichte 1850-; DISCOUNT-B.; Journalism -- Canada -- History -- 20th century; News agencies -- Canada -- History -- 20th century; Press -- Canada -- History -- 20th century; Massenmedien; Presse; Kanada